From M–P to MA–P: Multinationality alignment and performance - Powell, K Skylar (Journal of International Business Studies, 2014)
Rather than searching for a universal optimal level of multinationality for all firms, we argue that firm-specific attributes should result in firm-specific optimal levels of multinationality. Specifically, we draw upon transaction cost and internalization theory to argue that there will be different optimal levels of multinationality for individual firms, and if firms internalize foreign operations to an extent less than or greater than their individual optimal levels, transaction costs will increase and performance will decrease. To test this idea, we use transaction cost models in the context of large US law firms during the time period from 1986 through 2008 to estimate firm-specific optimal multinationality. Next, we test relationships between alignment with, or deviations from, firm-specific optimal levels of multinationality and performance (MA–P). Consistent with the MA–P hypothesis, insufficient and excessive levels of multinationality are both negatively related to financial performance. In addition, excessive multinationality is positively associated with downside performance risk. One key implication is that an MA–P approach may offer greater theoretical validity and clarity than traditional multinationality and performance (M–P) approaches.